2017
DOI: 10.20411/10.20411/pai.v2i2.204
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection of Macrophages: Implications for Pathogenesis and Cure

Abstract: Although CD4+ T cells represent the major reservoir of persistent HIV and SIV infection, accumulating evidence suggests that macrophages also contribute. However, investigations of the role of macrophages are often underrepresented at HIV pathogenesis and cure meetings. This was the impetus for a scientific workshop dedicated to this area of study, held in Cambridge, MA in January 2017. The workshop brought together experts in the fields of HIV/SIV immunology/virology, macrophage biology and immunology, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…These studies show for the first time that dopamine increases HIV infection in iMicroglia, and future studies using iMicroglia and iMacrophages will be extremely valuable as a more tractable platform in which to perform more complex molecular assays. Use of both macrophages and microglia is important because myeloid populations in the CNS are transcriptionally related (164), but microglia and macrophages are distinct cell types (165), and infection of both populations is central to the development of neuropathology (32)(33)(34)(35)(166)(167)(168)(169)(170).…”
Section: Discussionmentioning
confidence: 99%
“…These studies show for the first time that dopamine increases HIV infection in iMicroglia, and future studies using iMicroglia and iMacrophages will be extremely valuable as a more tractable platform in which to perform more complex molecular assays. Use of both macrophages and microglia is important because myeloid populations in the CNS are transcriptionally related (164), but microglia and macrophages are distinct cell types (165), and infection of both populations is central to the development of neuropathology (32)(33)(34)(35)(166)(167)(168)(169)(170).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that increased monocyte turnover better predicts the tempo of progression to AIDS in HIV-infected patients and SIV/SHIV-infected animals than declining level of CD4 + T cells alone [33,34]. Although CD4 + T cells are the major source of virus production in HIV-infected individuals, monocytes/macrophages contribute substantially to plasma viral load during late-stage of HIV disease when the levels of circulating CD4 + T cell are very low [35], even is associated with the gradual loss of nonprogressor status in the long-term nonprogressors (LTNPs) [36]. Our previous study showed that SHIV KU−1 -infected Chines RMs had the persistence of high virus loads (10 6 -10 8 viral RNA copies per ml) with a 1.5 years survival time, although their circulating CD4 + T cell levels were very low (10-250 cells/ul) over the course of infection.…”
Section: Discussionmentioning
confidence: 99%
“…While much is known about the roles of virus‐encoded envelope proteins and their roles in the infection mechanism, the functions of host‐encoded proteins on the virus surface have been given relatively little consideration in the prevailing paradigm 116 . Many cells known to bear TF are permissive to infection by clinically important enveloped viruses, including SARS‐CoV‐2, 117 HSV1, 118 Ebola, 119 influenza, 120 HIV, 121 dengue, 122 Zika virus, 123 HCV, 124 and others. It is reasonable to speculate that the surface of these and other viruses display TF, which may account for hemostatic and inflammatory symptoms associated with their infection.…”
Section: Tf and Virusesmentioning
confidence: 99%